Mgat4b-mediated selective N -glycosylation regulates melanocyte development and melanoma progression - Babita Sharma; Keerthic Aswin; Tanya Jain; Ayesha Nasreen; Ayush Aggarwal; Yogaspoorthi J. Subramaniam; Jeyashri Rengaraju; Srashti Jyoti Agrawal; Mayank Bhatt; Bhashkar Paul; Koushika Chandrasekaran; Aanchal Yadav; et al. (Proceedings of the National Academy of Sciences, 2025)
Melanocyte development involves key pathways that are often recapitulated during melanoma initiation, highlighting the importance of understanding these regulatory processes. Our study identifies mgat4b , a glycosyl transferase involved in selective N -glycan branching enriched in pigment progenitors, as a regulator of directional cell migration and establishment of melanocyte stem cell (McSC) pool during early development. Single cell RNA (scRNA) sequencing analysis in zebrafish upon targeted disruption of mgat4b reveals, that migratory melanocyte progenitors marked by galectin expression fail to persist. Lectin affinity proteomic analysis reveals the glycosylation of key melanocyte proteins GPNMB, KIT, and TYRP1 to be under the control of MGAT4B in melanocytic cells. Additionally, mislocalization of Junctional plakoglobin (JUP) explains the observed defects in cell adhesion and migration to be regulated by MGAT4B but not its isozyme MGAT4A. Our meta-analysis further reveals that melanoma patients with both the BRAF V600E mutation and elevated MGAT4B levels have significantly worse survival outcomes compared to those with only the BRAF V600E mutation. By leveraging the zebrafish MAZERATI platform to model BRAF V600E driver mutation in vivo, we show that mgat4b mutant cells fail to aggregate and initiate tumors. RNA profiling of the transformed melanocytes revealed cell–cell junction, adhesion, and ECM binding to be probable contributing factors that resulted in the failure of tumor onset. Using a small-molecule inhibitor we demonstrate that complex N -glycosylation inhibits early-stage melanoma progression. Our study underscores the importance of selective N -glycan branching in both melanocyte development and melanoma initiation, suggesting MGAT4B as a promising therapeutic target for melanoma treatment.